Global pandemic, economic and political crisis - Mora Ramirez, Rafael Félix (2021)
This paper studies the issue of the pandemic and its social, political and economic consequences. Its objective is to analyze the current situation and is based on the compilation and interpretation of philosophical texts. The main contribution of this essay is to criticize the most problematic aspects of capitalism that have come to light as a result of this crisis. Thus, it begins by exposing the control under which human life is currently. In this scenario, authoritarianism looms, destabilizing all possible democracy. Then, the errors of capitalism are shown and, immediately, the evident conflict between vital and economic values ​​that has occurred is reviewed. Finally, the consumerism of this society is analyzed.